The attitudes of National Security students towards sexting - Bereźnicka, Małgorzata (Східноєвропейський національний університет імені Лесі Українки, 2019)
The article discusses the problem of sexting. After introduction where the phenomenon is presented, some of the the results of author’s research are described. They survey was conducted among the students of National Security at the Pedagogical University of Cracow, and they were asked about their knowledge, experiences and also they shared their opinions on the subject. At the end there are key conclusions and postulates for the practice.
Keywords: sexting; communication; internet threats; attitudes; education